Understanding piety and theology in the culture of the West - Melleuish, Gregory, 1954- author. Link Link
1 online resource (184 pages).
Keywords: This book provides a new and original approach to the Western tradition, its foundations, and the implications of its particular development for understanding the contemporary world.Arguing that with the creation of writing in the Axial Age, tradition took a 'theological' form that placed emphasis on rationality and abstraction at the expense of 'piety,' which emerges from immediate experience and wonder. Exploring the development of the West and its culture through the dance between theology and piety, with theology always leading, the authors consider the contemporary ascendancy of theology in the dominance of universities and the decline of poetry, shedding light on the reflection of this tension in contemporary politics.An examination of interplay of conflicting tendencies in Western civilisation - and the need for balance - Understanding Piety and Theology in the Culture of the West will appeal to scholars with interests in social theory, historical sociology, and cultural studies.